Pengembangan Sistem Perekapan Laporan Transaksi Keuangan pada Jasa Percetakan Menggunakan Metode Extreme Programming - Nurul Muttaqin, Iswan; Setiawan, Ridwan (Jurnal Algoritma, 2025)
In an effort to improve financial management efficiency in the printing service business, this study developed a transaction report recording system using the Extreme Programming (XP) method, one of the agile software development approaches. The study was conducted at P2 Digital Printing in Garut, which previously faced issues with manual financial recording, such as input errors and report delays. This research fully implemented the XP stages, starting from planning (preparation of user stories and iteration plan), design (interface design, CRC cards, and UML diagrams), coding (implementation with pair programming, refactoring, and continuous integration), to testing (using Equivalence Partitioning and Acceptance testing). Test results showed that the system was able to manage transactions, accounts receivable and payable, and financial reports in real-time with higher accuracy compared to manual processes. The contribution of this study lies not only in the application of XP for a web-based financial system, but also in the integration of key features relevant to the needs of MSME-scale printing industry. Compared to previous studies that generally focused on educational institutions or cooperatives, this system provides a practical approach for printing businesses in terms of speed, data accuracy, and flexibility of use. These findings can serve as a reference for implementing XP in financial system development for similar sectors.